Lipase Production in Tray-Bioreactor via Solid State Fermentation under Desired Growth Conditions - Zahra Vaseghi; Ghasem D. Najafpour; Samaneh Mohseni; Soleiman Mahjoub; Maryam N. Hosseinpour (Iranica Journal of Energy and Environment, 2012)
Lipase was produced under desired growth conditions in a novel tray bioreactor using the fungus strain of Rhizopus oryzae. Several agricultural residues/products including sugarcane bagasse, wheat bran, corn meal, barely bran and equal mixtures of sugarcane bagasse with agricultural residues were applied as solid substrate. Lipase produced from the pure sugarcane bagasse showed higher activities than other substrates; which resulted enzyme activities of 155.76 and 138.37 U/gds for the top and middle trays respectively. Furthermore, the influence of carbon and nitrogen supplements was investigated. Addition of carbon sources as substrate was found to be ineffective, while lipase activity remarkably increased by supplementation of bagasse with adequate amount of nitrogen source. Among the nitrogen supplements, urea as a suitable nitrogen source was considered; as a result the average lipolytic activity of 229.355 U/gds was achieved. In addition, various concentrations of vegetable oils including canola oil, soybean oil, olive oil and castor oil were applied. The inducing effect of vegetable oil on lipase activity was investigated. Among them, olive oil and canola oil increased lipolytic activity of lipase with an average value of 192.26 and 183.57 U/gds, respectively.